A dynamic approach for teaching algorithms: Integrating immersive environments and virtual learning environments. Issue 5 (17th May 2017) - Nunes, Felipe B.; Herpich, Fabrício; Do Amaral, Érico M. H.; Voss, Gleizer B.; Zunguze, Manuel C.; Medina, Roseclea D.; Tarouco, Liane M. R.
Abstract: Utilization of technology in education lead to important changes in methods and techniques, where the use of virtual learning environments and virtual worlds provided a solution of a rich simulation and with a high level of interactivity and immersion. This article provides a summary of a research that searches integrate two different technologies [VLE and VW], by means of a solution called Sloodle. The main focus is demystify the use of this solution, introducing the mainly characteristics involved in the process of installation and insertion of this resources and evaluate the effectiveness of these resources as supporting tools in the teaching of algorithms in Computer Engineering course. The applications used in this research were OpenSimulator as Virtual World; Moodle as VLE; the online software IDEOne for the algorithm exposure and Sloodle. Analysis confirms that the utilization of virtual world combined with Moodle using Sloodle, it is a valid alternative to the process of teaching and learning, motivating the students and stimulating the feeling of immersion during the performance of activities. It allows identifying the difficulties to be overcome in this type of solution, like the utilization of Sloodle and technology limitations of their resources.